RELATIONSHIP BETWEEN MIDWIVES’ WORK MOTIVATION AND PERFORMANCE IN FAMILY PLANNING SERVICES - Shafira Tamara; Reny Nugraheni (International Journal of Patient Safety and Quality, 2025)
BackgroundFamily planning (FP) is a cornerstone of reproductive health and population control. However, disparities in FP service quality persist, often influenced by midwives’ motivation and organizational conditions. This study aimed to examine the relationship between midwives’ characteristics, work motivation, and performance in FP services. MethodsFP services in a community healthcare setting. Data were collected using a structured self-administered questionnaire adapted from Herzberg’s Motivation-Hygiene Theory Instrument and the Ministry of Health Midwifery Performance Evaluation Scale. The questionnaire assessed demographic characteristics, intrinsic and extrinsic motivation, and performance indicators using a 5-point Likert scale. Validity and reliability were confirmed (I-CVI > 0.80; Cronbach’s α > 0.85). Data were analyzed using Chi-square and Fisher’s exact tests with a significance level of p < 0.05. ResultsSignificant associations were found between motivational and organizational factors with midwives’ performance, including advancement (p = 0.000), achievement (p = 0.001), organizational policies (p = 0.020), incentives (p = 0.007), interpersonal relationships (p = 0.001), and working conditions (p = 0.001). Demographic variables such as age, education, and marital status were not significant (p > 0.05).ConclusionsMidwives’ performance in FP services is primarily influenced by intrinsic and extrinsic motivation rather than demographic factors. Enhancing motivation through fair incentives, supportive policies, and professional development is crucial to improve FP service quality and workforce sustainability.